Mujer de 42 años con hipertensión arterial estadio I y malos hábitos alimentarios - Andrade Zamora, Geoconda María (2018)
The present case study is based on a 42 years old female patient diagnosed with stage I high blood pressure three years ago, as well as her sisters and parents, who comes to the clinic for nausea and headaches, her blood pressure is measured and her values are 130 / 83 mmHg. General Objective: To improve the nutritional status of the patient through comprehensive nutritional care. Comprehensive nutritional assessment is made to the patient and is determined through the body mass index that presents obesity grade I with moderate cardiovascular risk, on the other hand, biochemical tests are performed and their values are normal, the physical examination shows the patient skin and normal mucous membranes, their dietary intake is excessive in energy and sodium, which is why DASH type feeding plan is carried out. Through the monitoring and follow-up that was done to the patient, favorable results were obtained; the patient started with a weight of 88 kg, in one month it decreased 2 kg; his initial BMI was 32.35 kg / mm2, he changed to 31.6 kg per month, he is still with Obesity, but there is improvement; his biochemical tests presented normal values; the blood pressure figures were initially 130/83 mmHg, at month their figures are 119/80 mmHg, it has dropped 11 mmHg; Changes were made in their food intake, through the feeding plan, energy 1550.15 kcal; 69.3 g proteins; fat 48.4 g; sodium 1018.2 mg, in this way it was possible to cover the nutritional requirements of the patient.